2020
DOI: 10.1371/journal.pone.0224051
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of interaction of an endofungal bacterium Serratia marcescens D1 with its host and non-host fungi

Abstract: Association of bacteria with fungi is a major area of research in infection biology, however, very few strains of bacteria have been reported that can invade and reside within fungal hyphae. Here, we report the characterization of an endofungal bacterium Serratia marcescens D1 from Mucor irregularis SS7 hyphae. Upon re-inoculation, colonization of the endobacterium S. marcescens D1 in the hyphae of Mucor irregularis SS7 was demonstrated using stereo microscopy. However, S. marcescens D1 failed to invade into t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…The result suggested that the two compounds may alter cell permeability and devote to the effecting of antibiotic. In addition, there are tremendous cases of successful restoring EHB to their host fungi by co-culturing GFP-labeled EHB with mycelium of the host fungi using low-nutrient media, such as 1/4 PDA and M9 medium (Partida-Martinez et al, 2007b;Arendt et al, 2016;Obasa et al, 2017Obasa et al, , 2019Baltrus et al, 2018;Hazarika et al, 2020). Arendt et al (2016) also reported that EHB colonization occurred more frequently and steadily under nutritional deficiency conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The result suggested that the two compounds may alter cell permeability and devote to the effecting of antibiotic. In addition, there are tremendous cases of successful restoring EHB to their host fungi by co-culturing GFP-labeled EHB with mycelium of the host fungi using low-nutrient media, such as 1/4 PDA and M9 medium (Partida-Martinez et al, 2007b;Arendt et al, 2016;Obasa et al, 2017Obasa et al, , 2019Baltrus et al, 2018;Hazarika et al, 2020). Arendt et al (2016) also reported that EHB colonization occurred more frequently and steadily under nutritional deficiency conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although not studied as extensively, several reports have also discussed prodigiosin and its activities against different fungal species [ 30 , 74 77 ]. Much like the two studies mentioned above, one group even looked at the ability of S. marcescens to protect Acris blanchardi (Blanchard’s Cricket frog) from B. dendrobatidis infections, reporting a slight, yet significant, increase in survival rates when compared against a pig mutant that is unable to synthesize this compound [ 77 ].…”
Section: Prodigiosin and Violacein As Antifungalsmentioning
confidence: 99%
“…PG enables S. marcescens D1 (an endofungal bacterium) to invade fungal hyphae and spread over the culture of F. oxysporum to result in mycelial death. [213].…”
Section: Antimicrobial Activitymentioning
confidence: 99%